2022
DOI: 10.1515/jpm-2022-0286
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal predictors of adverse perinatal outcome in congenital cytomegalovirus infection: a retrospective multicenter study

Abstract: Objectives To identify predictors of adverse perinatal outcome in congenital cytomegalovirus (CMV) infection. Methods In a multicenter study fetuses with congenital CMV infection diagnosed by PCR on amniotic fluid and normal prenatal imaging at the time of diagnosis were included. Primary outcome was the occurrence of structural anomalies at follow-up ultrasound or prenatal magnetic resonance imaging (MRI). Secondary outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…We have previously reported that in fetuses with congenital CMV infection and no structural anomalies detected at prenatal imaging, the risk of symptomatic infection and long-term sequelae related to the infection is lower when compared to what was reported in studies not considering the role of fetal imaging in predicting the prognosis [11,15]. Some anomalies related to congenital CMV infection, especially those involving neuronal migration, such as microcephaly, are difficult to identify prenatally, thus making prediction of the short-term outcome of these fetuses challenging [26,27].…”
Section: Clinical and Research Implicationsmentioning
confidence: 73%
See 1 more Smart Citation
“…We have previously reported that in fetuses with congenital CMV infection and no structural anomalies detected at prenatal imaging, the risk of symptomatic infection and long-term sequelae related to the infection is lower when compared to what was reported in studies not considering the role of fetal imaging in predicting the prognosis [11,15]. Some anomalies related to congenital CMV infection, especially those involving neuronal migration, such as microcephaly, are difficult to identify prenatally, thus making prediction of the short-term outcome of these fetuses challenging [26,27].…”
Section: Clinical and Research Implicationsmentioning
confidence: 73%
“…It remains the most common non-genetic cause of sensorineural hearing loss in infants [6][7][8]. Prenatal diagnosis of congenital CMV infection is accomplished through the identification of the virus in the amniotic fluid (AF) obtained at second trimester amniocentesis, at least 6-8 weeks after suspected maternal infection [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The risk of adverse events related to CMV once the infection is acquired by the fetus is low, thus requiring a large number of cases to demonstrate the efficacy of a given intervention. Furthermore, we could not perform subgroup analyses according to the magnitude of maternal viremia, type of CMV infection (primary vs non‐primary) or presence of ultrasound signs of the infection, as this information was not reported extensively in the included studies 31 . Finally, we could not elucidate the role of prenatal valacyclovir therapy in altering the risk of vertical transmission following maternal infection in the second and third trimesters of pregnancy because only one study with a very small number of included cases explored this outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal viral infections like Zika virus or cytomegalovirus may extensively impair prenatal brain. 6 , 7 The role of maternal SARS‐CoV‐2 illness in the prenatal maturation and growth of the central nervous system (CNS) is mostly unknown at this time but there are evidences in newborns and infants of the existence of neurological complication induced by the infection. 8 , 9 Although this hypothesized association, there are no studies evaluated the impact of SARS‐CoV‐2 disease on prenatal brain development.…”
Section: Introductionmentioning
confidence: 99%